Cortical activation during imagined walking for people with lower limb loss: a pilot study - Hunter, Susan W.; Motala, Aysha; Cronin, Alicia E.; Bartha, Robert; Viana, Ricardo; Payne, Michael W. (Frontiers in Human Neuroscience, 2023)
Each year in Canada, a substantial number of adults undergo limb amputation, with lower limb amputation (LLA) the most prevalent. Enhancing walking ability is crucial for optimizing rehabilitation outcomes, promoting participation and facilitating community reintegration. Overcoming challenges during the acute post-amputation phase and sub-acute rehabilitation necessitates alternative approaches, such as motor imagery and mental practice, to maximize rehabilitation success. However, the current evidence on activation patterns using motor imagery in individuals with LLA is limited. The primary objective was to assess the feasibility of observing brain activation during imagined walking in individuals with LLA utilizing 3T functional magnetic resonance imaging (fMRI). Eight individuals with LLA and 11 control subjects participated. Consistent with representations of the lower limbs, both control and amputee groups demonstrated bilateral activation in the medial surface of the primary motor and somatosensory cortices. However, individuals with lower limb amputations exhibited significantly greater activation during imagined walking, particularly in frontal regions and the medial surface of the primary motor and supplementary motor cortices. Furthermore, the volume of activation in the bilateral primary motor cortices was higher for participants with amputations compared to controls. The protocol developed in this study establishes a foundation for evaluating the effects of a gait training program that incorporates mental imagery alongside conventional rehabilitation practices, in contrast to standard care alone. This pilot investigation holds potential to enhance our understanding of brain plasticity in individuals with LLA and pave the way for more effective rehabilitation strategies to optimize functional recovery and community reintegration.